2023
DOI: 10.3389/fcomm.2022.920752
|View full text |Cite
|
Sign up to set email alerts
|

Disability does not negatively impact linguistic visual-spatial processing for hearing adult learners of a signed language

Taylor Renee Joyce,
David Quinto-Pozos,
Jenny L. Singleton
et al.

Abstract: The majority of adult learners of a signed language are hearing and have little to no experience with a signed language. Thus, they must simultaneously learn a specific language and how to communicate within the visual-gestural modality. Past studies have examined modality-unique drivers of acquisition within first and second signed language learners. In the former group, atypically developing signers have provided a unique axis—namely, disability—for analyzing the intersection of language, modality, and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…By contrast, when analyzing sign learning independently of iconicity, language age in a spoken language and not chronological age seemed to be the determining factor ( Schüler et al, 2021 ). Accordingly, Joyce et al (2023) have shown that language-based skills are crucial for sign learning in adults irrespective of cognitive (dis)abilities. This suggests that language acquisition per se does not require cognitive abilities that are necessary to recognize iconicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, when analyzing sign learning independently of iconicity, language age in a spoken language and not chronological age seemed to be the determining factor ( Schüler et al, 2021 ). Accordingly, Joyce et al (2023) have shown that language-based skills are crucial for sign learning in adults irrespective of cognitive (dis)abilities. This suggests that language acquisition per se does not require cognitive abilities that are necessary to recognize iconicity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, for adults with ID, translucent signs have been shown to be acquired more effectively and to be more functional than other signs ( Meuris et al, 2014 ). Overall, the signed modality does not seem to present any particular disadvantages for adults with cognitive disabilities when compared to neurotypical learners ( Joyce et al, 2023 ).…”
Section: Introductionmentioning
confidence: 93%
“…No participants with reported disabilities were included in this study, but see Joyce et al. (2023) for an analysis of a subset of data from the present analysis in addition to data from beginning‐level hearing ASL learners, including students who identify with one or more cognitive disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…One participant reported exposure from birth to American Sign Language from a Deaf signer in their home, and we included them because we could not attest to the quality or quantity of their signed language input; as such, this participant's data were treated the same as those of the other students in the classes. No participants with reported disabilities were included in this study, but see Joyce et al (2023) for an analysis of a subset of data from the present analysis in addition to data from beginning-level hearing ASL learners, including students who identify with one or more cognitive disabilities.…”
Section: Participantsmentioning
confidence: 99%